A Systematic Review and Meta-Analysis: The Long-Term Effects of Oral N-Acetylcysteine in Chronic Obstructive Pulmonary Disease - Nasikhatussoraya, Nova; Umam, Hamid Faqih; Rizkani, Ainingtyas Marda; Santoso, Hidayat (Nusantara Science and Technology Proceedings, 2024)
Chronic obstructive pulmonary disease (COPD) is one of the world's most prevalent causes of morbidity and mortality. About 5.6% of Indonesians have COPD. Most COPD patients have mucus hypersecretion and inadequate mucus clearance, leading to airway obstruction. N-acetylcysteine (NAC) is a mucolytic drug with antioxidant and anti-inflammatory effects. Long-term oral NAC use in COPD remains controversial. We searched four databases to analyze the effects of oral NAC in COPD over a minimum six-month treatment. The data was analyzed through Review Manager 5.4. Eight randomized controlled trials, comprising 3.187 patients, were selected for inclusion in the study. NAC had a lower risk of exacerbations (RR 0.78, 95% CI 0.66-0.93; p=0.005), whether at high dose (1200mg/day) or low dose (600mg/day). The risk is higher at the high dose (RR 0.90, p=0.04) than at the low dose (RR 0.70, p=0.0002). NAC did not affect FEV1 (mean difference 4.71, 95% CI -3.20-12.61; p=0.24), and adverse events were the same as with placebo (RR 1.14, 95% CI 0.78-1.67; p=0.51). Long-term oral NAC reduces the risk of COPD exacerbations at any dose and was well tolerated.